2016
DOI: 10.1038/srep36313
|View full text |Cite
|
Sign up to set email alerts
|

Identification of G8969>A in mitochondrial ATP6 gene that severely compromises ATP synthase function in a patient with IgA nephropathy

Abstract: Here we elucidated the pathogenesis of a 14-year-old Chinese female who initially developed an isolated nephropathy followed by a complex clinical presentation with brain and muscle problems, which indicated that the disease process was possibly due to a mitochondrial dysfunction. Careful evaluation of renal biopsy samples revealed a decreased staining of cells induced by COX and NADH dehydrogenase activities, and a strong fragmentation of the mitochondrial network. These anomalies were due to the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 50 publications
1
32
1
3
Order By: Relevance
“…No family members underwent histological or biochemical examinations. The threshold for manifesting disease is unknown for this particular variant, but healthy members in our family had much lower heteroplasmy levels in blood (< 1-18%) than the asymptomatic mother (49%) described by Wen et al [5]. Unfortunately, we had no opportunity to determine heteroplasmy of other tissues than described in the table, but heteroplasmy has been at a high level in all affected patients in all tissues studied (blood 61-96%, fibroblasts 85-96%, muscle 88-95%, kidney 89% and urine 79%) [1].…”
Section: Sircontrasting
confidence: 51%
See 1 more Smart Citation
“…No family members underwent histological or biochemical examinations. The threshold for manifesting disease is unknown for this particular variant, but healthy members in our family had much lower heteroplasmy levels in blood (< 1-18%) than the asymptomatic mother (49%) described by Wen et al [5]. Unfortunately, we had no opportunity to determine heteroplasmy of other tissues than described in the table, but heteroplasmy has been at a high level in all affected patients in all tissues studied (blood 61-96%, fibroblasts 85-96%, muscle 88-95%, kidney 89% and urine 79%) [1].…”
Section: Sircontrasting
confidence: 51%
“…We consider that the following facts support the pathogenic role of this variant: more than one previous independent reports, the base is evolutionarily conserved, the variant is heteroplasmic, the variant segregates with the disease in the pedigree, and ATP production was decreased in our patient. Furthermore, studies in yeast [5] confirm the pathogenicity of this variant.…”
Section: Sirmentioning
confidence: 74%
“…In addition to the patient with "MLASA-plus" the m.8969G>A mutation in MT-ATP6 has been reported previously, [10][11][12] but was not associated with CSA, despite a relatively high mutation burden in the peripheral blood of most of the other patients. The "MLASA-plus" index case, described Burrage et al, was a child with a complex multisystem disorder including failure to thrive, developmental delay, mitochondrial myopathy, lactic acidosis, sideroblastic anemia, a cardiac conduction defect, sensorineural hearing loss, epilepsy, agenesis of the corpus callosum, and stroke-like episodes.…”
Section: Letters To the Editormentioning
confidence: 55%
“…Wen et al presented a female with neuro-motor deficits and IgA nephropathy with an m.8969G>A mutation heteroplasmy of 61% in peripheral blood, 79% in urine, and 89% in renal tissue; a blood phenotype was not described. 11 Sallevelt et al briefly mentioned a patient who died at age 7½ months with 95% m.8969G>A heteroplasmy in blood, fibroblasts and skeletal muscle, but did not comment on the infant's phenotype. 12 Overall, these combined data would suggest that an allele burden of at least 80% in peripheral blood leukocytes is required to manifest an overt CSA phenotype.…”
Section: Letters To the Editormentioning
confidence: 99%
“…The kidney is an organ with high energy demands and a consequent abundance of mitochondria. Mitochondrial injury plays an important role in the pathogenesis of various kidney diseases, including acute kidney injury [6], chronic kidney disease [7][8][9][10], obesity-related hyperfiltration [11], and glomerulonephritis (GN) [12][13][14][15][16]. Recently, we demonstrated that mitochondrial injury is involved in early-stage glomerular inflammation prior to pathological changes in immunoglobulin A nephropathy (IgAN) by measuring urinary mitochondrial DNA (mtDNA) [17], which is used as a surrogate marker of mitochondrial injury in various kidney diseases [18][19][20].…”
Section: Introductionmentioning
confidence: 99%